Correlation analysis of saliva volume and salivary pH on dental caries status in children aged 11-12 years using the HI BOGI application: a cross sectional study - Fadilah, Rina Putri Noer; Rivmawati, Lestary; Nawawi, Azkya Patria; Supriatna, Andi; Pribadi, Ari Prayogo (Universitas Padjadjaran, 2025)
Introduction: Oral health is a key indicator of overall wellbeing, with dental caries remaining one of the most prevalent oral health problems in Indonesia. Saliva, particularly its volume and pH, is an important host factor influencing caries development. This study aims to analyze the association between saliva volume and salivary PH and dental caries among schoolchildren using the HI BOGI application. Methods: An analytic observational study with a cross-sectional design was conducted among 11–12-year-old students from six randomly selected primary schools in Cimahi City (n=285). Saliva volume and pH were measured, and dental caries experience was assessed using the HI BOGI application. Data were analyzed using the Spearman rho correlation test. Results: Children with lower saliva volume and more acidic saliva pH demonstrated higher DMF-T scores. Correlation tests indicated a relationship between low salivary volume and dental caries incidence (rs= –0.117; p≤0.05) and between salivary pH and caries (rs= –0.287; p≤0.05). Conclusion: saliva volume and acidic saliva pH are significant risk factors for dental caries incidence among 11–12-year-old children as identified through the HI BOGI application assessment.